Chattermarked garnets and heavy minerals from the Late Paleozoic glacial deposits of southeastern Brazil - Gravenor, C. P. (Canadian Journal of Earth Sciences, 1980)
Heavy mineral suites from Late Paleozoic tillites from the southeastern part of the Paraná Basin are dominated by garnet. An analysis of the heavy minerals and chattermark trails found on the garnets suggests that the glacial sediments were transported over long distances, probably as a result of having been recycled many times.The heavy mineral suites are more complex than those found in the intensively glaciated regions of Australia and South Africa. This observation combined with an analysis of the chattermark trails on garnets suggests that glaciation was not as intense nor did it last as long as the glaciation over southern Africa, Antarctica, and Australia. The glaciers which deposited the tillites in the eastern side of the Paraná Basin were probably centered in southern Africa and moved northward and westward penetrating the eastern side of the Paraná Basin.